Standard patient training versus Vik-Asthme chatbot-guided training: ‘AsthmaTrain’ – a protocol for a randomised controlled trial for patients with asthma - Arnaud Bourdin; Nicolas Molinari; Carey Meredith Suehs; David Galeazzi; Isabelle Vachier; François Vaast; Fanny Cardon (BMJ Open)
Introduction Therapeutic education for patients with asthma has been shown to reduce asthma morbidity. The high availability of smart phones provides the opportunity to furnish patient training via specifically designed chatbot applications. The goal of this protocol is to perform a first pilot comparison of traditional face to face versus chatbot-guided patient therapeutic education programmes for patients with asthma.Methods and analysis Eighty adult patients with a physician-confirmed diagnosis of asthma will be enrolled in a two-parallel-arm, randomised (1:1) controlled pilot trial. A single-Zelen consent procedure is deployed to first enrol all participants in the comparator arm, that is, the standard patient therapeutic education programme at the University Hospitals of Montpellier, France. This means of patient therapeutic education is based on reoccurring interviews and discussion with qualified nursing staff as per usual care. Following baseline data acquisition, randomisation will be performed. Those patients randomised to the comparator arm will not be informed of the second arm. Those patients randomised to the experimental arm will be proposed access to a specifically designed chatbot (Vik-Asthme) as the second tested means of patient training (refusals continue with standard training, though analysed as intention to treat). The primary outcome is change in the total Asthma Quality of Life Questionnaire score at the end of follow-up (6 months). Secondary outcomes cover asthma control, spirometry, general health status, programme adherence and burden for medical staff, exacerbations and medical resource use (medications, consults, emergency visits, hospitalisation and intensive care).Ethics and dissemination This study (‘AsthmaTrain’ protocol version 4–20220330) has been approved by the Committee for the Protection of Persons Ile-de-France VII on 28 March 2022 (reference number 21.03617.000059). Enrolment began on 24 May 2022. Results will be published in international peer-reviewed journals.Trial registration number NCT05248126.